UNRAVELLING THE COMPLEXITIES OF THE DIGITAL ECONOMY: THE CONVERGENCE OF TECHNOLOGY AND INNOVATION AS THE ENGINE OFNEW ECONOMIC GROWTH - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The digital economy has become a complex phenomenon fuelled by the convergence of technology and innovation. Advances in information and communication technology have changed the way businesses operate, creating new business models and opening up opportunities for economic growth. Innovation is key in unravelling the complexity of the digital economy, enabling companies to adapt quickly, create added value and improve operational efficiency. To optimally utilise the potential of the digital economy, collaboration and synergy between the government, industry, academia and society are required. The government needs to create a conducive environment for innovation, industry needs to continue to innovate and adapt, academia needs to play an active role in research and development, and society needs to be open to innovation. With strong synergy and collaboration, the complexity of the digital economy can be unravelled and utilised as a new motor of sustainable economic growth.